PENGARUH MOTIVASI BERPRESTASI TERHADAP PRODUKTIVITAS KERJA PEGAWAI NEGERI SIPIL (PNS) (Jurnal Tata Kelola Pendidikan, 2019)
This research aims to obtain overview an effect of achievement motivation on theproductivity of government employe in the center for teacher and education personeldevelopment of mechanical and industrial engineering Bandung. This research usesdescriptive method with quantitative approach. Data collection techniques using a closedquestionnaire that was distributed to 66 government employe in PPPPTK BMTI Bandungas a research sample. The hypothesis proposed is the exixtence of a positive and significanteffect between achievement motivation (X) on the productivity (Y) of government employein PPPPTK BMTI Bandung. Weight Means Score (WMS) calculation results show thatachievement motivation scores of 3,36 are included in the very high category and workproductivity get a value of 3,46 included in the very high category. To test the researchhypothesis several steps were carried out, namely correlation analysis between variabelsusing Pearson Product Moment obtained a result of 0,821 wich showed the correlation ofreliation between the 2 variables was at the level of a positive and very strong relation.Then the significance test using t test result obtained thitung 11,495>ttabel 1,997 meansthat there is a significant relation between the X variabel and the Y variable. The coefficientof determination test result obtained that the variable X affects the Y variable by 67,4%and the rest is influensced by other variables not examined in this research, while in theregression analysis obtained by (Y ) ̂= 16,585 + 0,821X equation this means that if thereis an increase of one in the Y variable it will be followed by an increase of 0,821 in the Xvariable. The conclusion of this study is that there is a significant and positive influencebetween achievement motivation on the productivity of government employe in the centerfor teacher and education personel development of mechanical and industrial engineeringBandung.
Keywords: Achievement Motivation; Work Productivity; Civil Servants